THE IMPLEMENTATION OF PROJECT-BASED LEARNING APPROACH IN TEACHINGWRITING NEWS ITEM TEXT TO THE TENTH GRADERS OF SMA I KARANGANTRENGGALEK - ARDIANTI, SEPTINA (RETAIN : Journal of Research in English Language Teaching, 2013)
Penelitian ini bertujuan untuk mendeskipsikan penerapan pembelajaran melalui projek pada siswa kelas X SMA 1 Karangan Trenggalek dalam pengajaran menulis teks news item, untuk mendeskripsikan respon siswa terhadap penerapan pembelajaran melalui projek dalam pengajaran menulis teks news item dan. untuk mendeskripsikan ketrampilan siswa dalam menulis teks news item selama penerapan pembelajaran melalui projek. Penelitian ini dirancang sebagai sebuah laporan dalam bentuk deskriptif qualitative. Hasil penelitian ini menunjukan bahwa aktifitas pembelajaran melalui projek telah diterapkan di dalam kelas dan sebagai sebuah pendekatan pada siswa. Pembelajaran melalui projek sangat efektif membantu siswa menulis teks news item dengan baik. Pembelajaran melalui projek juga mampu memotivasi siswa untuk lebih kreatif dan meningkatkan kemampuan belajar dalam grup dalam proses pembelajaran di kelas. Kata Kunci: Steps Chain, ketrampilan berbicara bahasa Inggris, teks prosedur, siswa kelas tujuh. Abstract This study was conducted to describe the implemention of Project-Based Learning (PBL) Approach in teaching writing news item text to the tenth graders of SMA 1 Karangan Trenggalek, to describe the students’ response toward the implementation of Project-Based Learning approach in teaching writing news item text and to describe the students’ news item writing text during the implementation of Project- Based Learning approach in teaching writing news item text. This research was done by using descriptive qualitative. The subjects of the study were X IPA1 students of SMA 1 Karangan Trenggalek.. The result of the study shows that PBL approach has successfully been implemented in teaching news item text, because the students were active during the teaching and learning process. It can be seen from the result of the study that PBL approach can help the students to write news item text better. PBL also motivate students to be more creative, it also help them to have better ability in group working. Key words: news item text, Project-Based Learning, writing.